JUSTIFYING A LARGE PART OF PHILOSOPHY. Issue 51 (12th February 2019) - Frances, Bryan
Abstract : I explain why research in non-applied, non-interdisciplinary, non-historical philosophy is worthwhile. The key move in the explanation is the realization that many philosophical problems can be put in the form of a set of highly plausible yet apparently jointly inconsistent claims regarding a fundamental notion.